1999
DOI: 10.1007/bf02562302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of third trimester consumption of eggs high in docosahexaenoic acid on docosahexaenoic acid status and pregnancy

Abstract: Summary High‐DHA eggs appear to be a practical way to increase maternal DHA status. The data suggest that high‐DHA eggs could decrease the incidence of preterm and low‐birth‐weight births, and this could be tested in a study with more statistical power. The neurodevelopment of infants from women fed low‐ and high‐DHA eggs could also provide helpful information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This is consistent with a number of studies that have demonstrated enhanced neonatal DHA status after maternal supplementation with fish oil (Connor et al, 1996;Helland et al, 2001;Velzing-Aarts et al, 2001) or DHA-rich eggs (Borod et al, 1999). We observed a strong linear relationship between maternal and neonatal PUFA profiles in both the fish oil-supplemented group and the control group, as seen previously in both unsupplemented Matorras et al, 1999) and supplemented women (van Houwelingen et al, 1995;Connor et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a number of studies that have demonstrated enhanced neonatal DHA status after maternal supplementation with fish oil (Connor et al, 1996;Helland et al, 2001;Velzing-Aarts et al, 2001) or DHA-rich eggs (Borod et al, 1999). We observed a strong linear relationship between maternal and neonatal PUFA profiles in both the fish oil-supplemented group and the control group, as seen previously in both unsupplemented Matorras et al, 1999) and supplemented women (van Houwelingen et al, 1995;Connor et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…[4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] No similar systematic reviews were found during the search process. Twenty RCTs were excluded for various reasons.…”
Section: Resultsmentioning
confidence: 99%
“…One study (9) had two independant arms (listed as earl-PD and earl-IUGR) to signify previous pregnancy with PTB or intrauterine growth restriction (IUGR), respectively, which quoted our prescribed outcomes and was considered as two independent trials in this review (Table 1). Of the 10 studies excluded (Table 2), three were based on the same population as reported in another study (12)(13)(14), four reported no useful data according to the outcome (15)(16)(17)(18) and three used a combination of n-3 fatty acids and another intervention that could not be considered separately (19)(20)(21). The four included trials comprised 921 women with respect to data on gestational age and 1 187 women with respect to data on birthweight.…”
Section: Trial Selectionmentioning
confidence: 99%
“…In all studies, the intervention was DHA, and in the Danish and European studies an additional amount of eicosapentaenoic acid (EPA) was part of the intervention. In two studies, the main outcome was gestational age, while data on PTB and birthweight were presented as secondary (12) Abstract of subsequently published randomized trial, included in the review (11) The intervention was micronutrients in addition to n-3 fatty acids. The selected n-3 fatty acid was α-linolenic acid, which is a precursor of docosahexaenoic acid, and the dose was not specified Harper et al (2010) (19) The intervention was progesterone in addition to n-3 fatty acids outcomes (10,11).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%